Effects of long-term adapted physical training on functional capacity and quality of life in older adults with Parkinson's disease - Oussama Gaied Chortane; Elmoetez Magtouf; Wael Maktouf; Sabri Gaied Chortane (AIMS Neuroscience)
BackgroundParkinson's disease (PD) remains incurable and its prevalence is increasing as the population ages. Although physical activity is considered a therapeutic treatment to slow the progression of the disease, it is considered to be an effective non-pharmacological adjuvant to medication to improve the symptom management.MethodsThe training program was offered for all the participants (N = 50) in three non-consecutive sessions per week for 60 minutes and a total duration of 12 to 16 months. Each session is composed of warming up, adapted boxing training exercises, muscle building and resistance exercises, and returning to calm. For the measurement of physical capacities, the following tests were administered: the Fullerton Advanced Balance Scale (FAB), Timed Up and Go (TUG), and the 30-second chair lift test (TLC30). With regard to quality of life, the Parkinson's Disease Questionnaire of 39 questions (PDQ-39) was used. The participants (age range from 60 to 80 years) were divided following the results of the Parkinson disease severity (Questionnaire Hoehn and Yahr; H&Y) into two groups (H&Y 1–2: mild to moderate symptoms; H&Y 3–4: moderate to severe symptoms).ObjectiveThe aim of this research was to assess the long-term effects (12 to 16 months) of a community-wide adapted physical program on the physical capacity and quality of life of people with Parkinson disease.ConclusionIn view of the results, adapted physical training appears to be beneficial for physical capacity and life quality and considered to be an important approch for maintaining the physical and mental capacities and slowing down the proression of neurodegenrative disease.